Computational study of mass reduction of a conceptual microsatellite structural subassembly utilizing metal perforations - Salman Dawood, Sarmad Dawood; Harmin, Mohammad Yazdi; Mohd Harithuddin, Ahmad Salahuddin; Chia, Chen Ciang; Mohd Rafie, Azmin Shakrine (The Aeronautical and Astronautical Society of the Republic of China, 2021)
A subassembly from the structural subsystem for a conceptual microsatellite designed for earth resources missions underwent normal modes analyses, after implementing an alternative approach to mass reduction, other than implementing advanced space qualified materials. This approach involved developing and implementing a set of geometric patterns that imposed upon certain components of the structural subassembly as perforation patterns, hence achieving mass reduction through straightforward material removal. This approach was proposed to introduce a relatively low-cost and easily implemented mass reduction methodology, which can be utilized by entities with little or no infrastructure and experience in advanced materials, though aspiring to develop their own satellite developing capabilities. The subassembly was the primary load path through which the launch loads pass, the so-called central box, consisting of four Aluminum 6061 identical planar plates, fastened together by titanium fasteners. The subassembly's fundamental natural frequency and attendant mode shape, for all cases, were computed utilizing the finite element method. The current work's approach to mass reduction resulted in an approximate 20% percent reduction in mass from the unperforated case, depending upon the exact thickness value employed for the subassembly plates, hence indicating that the perforation approach is valid.